Morphometry and Water Quality Study of Pit Lakes in Coal Mines - Widara, Maharani Rindu; Cahyadi, Teddy Agung (Jurnal Teknologi dan Manajemen, 2025)
After mining is completed, the remaining pits that cannot be restored to their original condition become artificial pit lakes. Pit lakes are used in reclamation efforts after mining activities. An in-depth analysis of the pit lake generated in a previously mined area is required, specifically concentrating on evaluating the water volume, morphometry, and water quality of the pit lake. Management strategies required for achieving sustainable development. Paringin Lake was found to have a surface area of 19.5 hectares, a maximum depth of 33 metres, and an underwater retention duration of 303 days. A 1.25 volume shift in the Paringin pit lake indicates a shallow bottom state. The Paringin pit lake is relatively stable and not prone to wind-induced churning, as indicated by the relative depth calculation of 6.6%. According to calculations using the Storet method, Paringin Pit Lake has minor contamination. The distant location of the Paringin pit lake is the cause of this. The results suggested that Pit Lake Paringin has the potential for utilization in aquatic tourism and aquaculture.